Is telehealthcare for heart failure patients cost-effective? An economic evaluation alongside the Danish TeleCare North heart failure trial - Anne Sig Vestergaard; Louise Hansen; Sabrina Storgaard Sørensen; Morten Berg Jensen; Lars Holger Ehlers (BMJ Open)
Objective This study aimed to assess the cost-effectiveness of telehealthcare in heart failure patients as add-on to usual care.Design A cost-utility analysis was conducted from a public payer perspective alongside the randomised controlled TeleCare North trial.Setting The North Denmark Region, Denmark.Participants The study included 274 heart failure patients with self-reported New York Heart Association class II-IV.Interventions Patients in the intervention group were provided with a Telekit consisting of a tablet, a digital blood pressure monitor, and a scale and were instructed to perform measurements one to two times a week. The responsibility of the education, instructions and monitoring of the heart failure (HF) patients was placed on municipality nurses trained in HF and telemonitoring. Both groups received usual care.Outcome measures Cost-effectiveness was reported as incremental net monetary benefit (NMB). A micro-costing approach was applied to evaluate the derived savings in the first year in the public health sector. Quality-adjusted life-years (QALY) gained were estimated using the EuroQol 5-Dimensions 5-Levels questionnaire at baseline and at a 1-year follow-up.Results Data for 274 patients were included in the main analysis. The telehealthcare solution provided a positive incremental NMB of £5164. The 1-year adjusted QALY difference between the telehealthcare solution and the usual care group was 0.0034 (95% CI: −0.0711 to 0.0780). The adjusted difference in costs was -£5096 (95% CI: −8736 to −1456) corresponding to a reduction in total healthcare costs by 35%. All sensitivity analyses showed the main results were robust.Conclusions The TeleCare North solution for monitoring HF was highly cost-effective. There were significant cost savings on hospitalisations, primary care contacts and total costs.Trial registration number ClinicalTrials.gov: NCT02860013.